SafePsych: improving patient safety by delivering high-impact simulation training on rare and complex scenarios in psychiatry - Bronwyn Reid-McDermott; Dara Byrne; Eimear McMahon; Anne M Doherty; Kezanne Tong (BMJ Open Quality)
Introduction Despite an evidence base demonstrating simulation to be an effective medical education tool, it is not commonly used in postgraduate psychiatry training as it is in other medical specialties.Objective This paper outlines the development and effectiveness of a hybrid-virtual simulation-based workshop designed to improve patient care by improving clinical skills of non-consultant hospital doctors (NCHDs) in detecting and managing rare and complex psychiatric emergencies.Methods Three clinical vignettes based on near-miss psychiatric cases were developed by a multidisciplinary team of physicians and nurses in psychiatry and experts in simulation-based medical education. The workshop, ‘SafePsych’ was delivered in a simulation laboratory while and broadcast via Zoom video-conferencing platform to observers. Debriefing followed each clinical scenario. Participants completed preworkshop and postworkshop questionnaires to evaluate clinical knowledge.Results The workshop was attended by consultants (n=12) and NCHDs in psychiatry and emergency medicine (n=19), and psychiatric nurses (n=5). In the psychiatry NCHD group, test scores significantly improved following the workshop (p<0.001). There were significant improvements in the test scores with a mean difference of 2.56 (SD 1.58, p<0.001). Feedback from participants and observers was positive, with constructive appraisals to improve the virtual element of the workshop.Conclusion Simulation-based training is effective in teaching high risk, rare complex psychiatric cases to psychiatry NCHDs. Further exploration of the learning needs of nursing staff is required. Future workshop delivery is feasible in the COVID-19 environment and beyond, using a virtual element to meet social distancing requirements while enhancing the reach of the training.